Masters athletes: Exemplars of successful aging? - Geard, D.; Reaburn, P.; Rebar, Amanda; Dionigi, R. (Human Kinetics Inc, 2017)
Â© 2017 Human Kinetics, Inc. Global population aging has raised academic interest in successful aging to a public policy priority. Currently there is no consensus regarding the definition of successful aging. However, a synthesis of research shows successful aging can be defined as a late-life process of change characterized by high physical, psychological, cognitive, and social functioning. Masters athletes systematically train for, and compete in, organized forms of team and individual sport specifically designed for older adults. Masters athletes are often proposed as exemplars of successful aging. However, their aging status has never been examined using a comprehensive multidimensional successful aging definition. Here, we examine the successful aging literature, propose a successful aging definition based on this literature, present evidence which suggests masters athletes could be considered exemplars of successful aging according to the proposed definition, and list future experimental research directions.